Effect of scan delay on measurements of an occlusal pressure sensitive film: An in-vitro study - Tong-Mei Wang; Yung-Hsiang Chang; Tsung-Chieh Yang; Li-Deh Lin (Elsevier, 2022)
Background/purpose: While scan delay may affect the measurements of an occlusal pressure-sensitive film, Dental Prescale II (DPS2), the duration of scan delay was rarely reported in previous studies. This study aimed to clarify the effect of scan delay on DPS2 measurements. Materials and methods: Two experiments were performed to clarify the effect of 0- to 10-min scan delay after DPS2 force registration. In both experiments, 11 loads were applied separately on a DPS2 film at 1-min interval between loads. Scanning was performed immediately after the 11th load in the 1-scan experiment and immediately after each load in the 11-scan experiment. A 300-N load was applied with a universal testing machine on 10 DPS2 films in each experiment and the DPS2 film was scanned with Bite Force Analyzer. Load measured, contact area, mean pressure, and maximum pressure were reported. ANOVA and Scheffé test were performed to compare the effect of number of scans and delay scan duration on these measurements with the critical value set at P ≤ 0.05. Results: Number of scans had no significant effect on the four measurements studied. However, all measurements, except contact area, were significantly affected by scan delay; the longer the scan delay, the greater the increase in measurements. The load measured showed a rapid increase (13%) in the first 2 min, followed by a gradual increase from 2 min to 10 min (10%). Conclusion: Scan delay does affect DPS2 measurements, and it is important to standardize and report scan delay duration in clinical studies.